?DETERMINATION OF AVAILABLE BORON CONTENT OF THE SOILS OF JOS PLATEAU, NIGERIA (Biological Sciences - PJSIR, 1995)
The available boron content of sixteen soilsamplesfrom an agriculturalareaofJos Plateau werecritically inves- tigated.The hotwaterextractableboron(availableboron)contentswerefoundtorangefrom6.0ppmto 14.5 ppm.These values lie outside therange (0.5-5.0 ppm)requiredby most plantsandmay provetoxic ifcorrections are notapplied. Theboroncontentofthetopsoilswereslightlyhigherin allcasesthaninthesub-soils.Relationshipbetweentheavailable boron andthepHofthesoilsamplesfollowedtheusualtrendi.e.theboroncontentofthesampleswerefoundtoincrease as the soils pH increased.